Highly Active and Durable Pt72Ru28 Porous Nanoalloy Assembled with Sub‐4.0 nm Particles for Methanol Oxidation - Zhao, Wei‐Yue; Ni, Bing; Yuan, Qiang; He, Pei‐Lei; Gong, Yue; Gu, Lin; Wang, Xun (Advanced energy materials, 2017)
The main challenges to the direct methanol fuel cells are the activity and durability of electrocatalysts. To alleviate such issues, a recently proposed strategy introduces an exotic element to form Pt‐based alloy nanostructures. This study reports a green route to prepare porous flowerlike Pt72Ru28 nanoalloys assembled with sub‐4.0 nm particles. The peak current density and mass activity on these as‐synthesized porous flowerlike Pt72Ru28 nanoalloys can be increased to 10.98 mA cm−2 and 1.70 A mg−1 Pt for methanol oxidation in acidic medium. They are respectively 4.19/3.54, 4.27/5.0, and 5.74/1.73 times those on the commercial Pt black, Pt50Ru50 black, and Ru50Pt50/C. These porous flowerlike Pt72Ru28 nanoalloys have a much higher long‐term durability than commercial Pt black, Pt50Ru50 black, and Ru50Pt50/C. More significantly, the porous Pt72Ru28 bimetallic nanoalloys have long‐term solvent durability after immersion in water for 16 months. The peak current density and mass activity on porous Pt72Ru28 nanoalloys are still 7.76 mA cm−2 and 1.2 A mg−1 Pt. These experimental results show an effective approach to the development of PtRu nanoalloys as electrocatalysts with substantially enhanced activity and durability for direct methanol fuel cells. Porous Pt72Ru28 nanoalloys assembled with sub‐4.0 nm particles are successfully prepared. Specific activity and mass activity of Pt72Ru28 nanoalloys can boost to 10.98 mA cm−2 and 1.70 A mg−1 Pt toward methanol oxidation. After being kept for 16 months in water, the specific activity on Pt72Ru28 nanoalloys is 2.96, 3.02, and 4.06 times that on commercial Pt black, Pt50Ru50 black, and Pt50Ru50/C, respectively.